The Emerging Role of RNA Modifications in the Regulation of Antiviral Innate Immunity - Tong, Jie; Zhang, Wuchao; Chen, Yuran; Yuan, Qiaoling; Qin, Ning-Ning; Qu, Guosheng (Frontiers in Microbiology, 2022)
Posttranscriptional modifications have been implicated in regulation of nearly all biological aspects of cellular RNAs, from stability, translation, splicing, nuclear export to localization. Chemical modifications also have been revealed for virus derived RNAs several decades before, along with the potential of their regulatory roles in virus infection. Due to the dynamic changes of RNA modifications during virus infection, illustrating the mechanisms of RNA epigenetic regulations remains a challenge. Nevertheless, many studies have indicated that these RNA epigenetic marks may directly regulate virus infection through antiviral innate immune responses. The present review summarizes the impacts of important epigenetic marks on viral RNAs, including N6-methyladenosine (m6A), 5-methylcytidine (m5C), 2’-O-methylation (2’-O-Methyl), and a few uncanonical nucleotides (A-to-I editing, pseudouridine), on antiviral innate immunity and relevant signaling pathways, while highlighting the significance of antiviral innate immune responses during virus infection.